Toxicidade do cloridrato de doxorrubicina na dose de 120mg/m², em cadelas com tumor venéreo transmissível - Viéra, Rafaela Bortolotti [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Doxorubicin (DOX) is considered one of the most active agent avaliable for chemotherapy treatment of cancer, in addition to be one of the most antineoplastic drug used for the treatment of canine Transmissible Venereal Tumor resistant to vincristine. For a better understanding of the side effects caused by the use of DOX in dogs, we did an study composed by 10 domestic, female, mixed breed dogs with Transmissible Venereal Tumor of natural ocurrence, diagnosed by cytology, with no evidence of metastasis and without previous chemotherapy treatment, that received DOX in dose of 30 mg/m² ou 1 mg/kg for animals weighing less than 15 kg. Were evaluated the effects of DOX in the peripheral blood and bone marrow, blood biochemistry and tumor cytotoxicity response. In order to standardize the toxicity level, we applied the terminology based on the addapted tables of the veterinary co-operative oncology group-Common terminology criteria for adverse events - VCOG-CTCAE). Statistical data were analyzed by the variance method with repeated measures; linear regression, quadratic and cubic and when there was a significant difference between means (P <0.05), these were compared by Tukey test. The values of red blood series did not change significantly between moments; the white blood cell count was significantly higher at baseline (M0) when compared to the 14th day after the fourth session (M7); segmented neutrophils had significant reduction on the 14th day after the first and third chemotherapy session when compared with the initial moment; lymphocytes, basophils, eosinophils and neutrophils rods did not differ between the moments. In The myelogram, rubrícitos, metarubrícitos ratio, showed a significant increase 21 days after the end of chemotherapy (M8), and myeloid: erythroid relationship showed significantly decreased after the treatment (M8); neutrophils rods and segmented neutrophils showed reduced values in M8. Biochemical parameters ...

O Cloridrato de Doxorrubicina (DOX) é considerado um dos agentes mais ativos disponíveis para o tratamento quimioterápico do câncer, além de ser um dos antineoplásicos mais utilizados para o tratamento de tumor venéreo transmissível canino resistente à vincristina. Com intuito de melhor conhecimento dos efeitos adversos promovidos pelo uso da DOX em cães, foi delineado um estudo composto por um grupo de 10 cães domésticos, do sexo feminino, sem raça definida, com peso entre 4,5 e 24 kg e idade média de 5 anos, portadores de TVT de ocorrência natural, confirmados por avaliação citológica, sem metástases clinicamente detectáveis ou quimioterapia prévia, que receberam o Cloridrato de Doxorrubicina na dose de 30 mg/m2 ou 1mg/kg para os animais com peso inferior a 15kg. Foram avaliados os efeitos da DOX sob o sangue periférico e medula óssea, além de avaliação da bioquímica sanguínea e resposta de citotoxicidade tumoral. A determinação da toxicidade gerada pelo tratamento quimioterápico com DOX baseou-se nos critérios de efeitos adversos estabelecidos pelo consenso da cooperativa de oncologia veterinária (VCOOG). Os dados obtidos foram submetidos à análise estatística pelo método de variância com medidas repetidas; regressão linear, quadrática e cúbica e quando houve diferença significativa entre médias (P < 0,05), estas foram comparadas entre si pelo teste de Tukey. Os valores da série vermelha do sangue não apresentaram alterações significativas entre os momentos; a contagem de leucócitos totais foi significativamente maior no momento inicial (M0) quando comparada com o 14º dia após a quarta sessão (M7); os neutrófilos segmentados apresentaram redução significativa no 14º dia após a primeira e após a terceira sessão quimioterápica quando comparados com o momento inicial; os valores de linfócitos, basófilos, eosinófilos e neutrófilos bastonetes não diferiram entre os momentos...
Keywords: Cão; Tumores em animais; Quimioterapia veterinaria; Agentes antineoplasicos; Doxorrubicina; Drogas - Efeitos colaterais; Chemotherapy